INVESTIGATING THE ADAPTABILITY OF CHATGPT FOR GENERATING REFERENCE DIALOGUES FOR HIGHER-LEVEL ENGLISH LEARNERS - Maulidyah, Difa Salsa; Anam, Syafi'ul; Nugroho, Him'mawan Adi (Universitas Muhammadiyah Makassar, 2025)
English proficiency can enhance non-native speakers' educational experience by providing them access to a wide range of materials, international conferences, and chances for collaboration. However, acquiring a language can present significant challenges, especially for people who are not native English speakers and those who enter the education system from other nations. The utilization of Artificial Intelligence (AI) and fully automated interactive spoken language (SDS) has the potential to enhance student engagement and facilitate improvements in oral contact and communication. The Chatbot feature of ChatGPT, an AI website, has the potential to enhance language learning by promoting active participation and improving educational achievements. Nevertheless, the efficacy of ChatGPT in catering to the needs of second language (L2) learners can be constrained by their distinct linguistic demands. This project aims to investigate the capacity of ChatGPT to produce reference dialogues tailored for advanced English learners and examine the potential enhancement of dialogue quality through prompting strategies. This study used a mixed method study, which distributed a survey questionnaire and conducted semi-structured interviews with the responders to determine the best prompting technique used in ChatGPT for generating reference dialogue. Then, the finding of this research showed that most students had a positive perception of using ChatGPT to generate dialogue references. However, some of them had a negative perception in some parts of using ChatGPT to generate dialogue references. Furthermore, ChatGPT was valuable and helpful in generating dialogue references, which helped the students be more confident when they wrote a conversational dialogue.